2015
DOI: 10.5539/gjhs.v8n5p211
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Chlorhexidine Solution and Swab With Toothbrush and Toothpaste Effect on Preventing Oral Lesions in Hospitalized Patients in Intensive Care Unit

Abstract: Background:Maintaining of oral hygiene has been known as one of the basic tasks of nurses working at intensive care unit. This study aimed to compare the effectiveness of chlorhexidine solution with toothbrush in prevention of oral lesions or ulcers in the different parts of the mouth.Methods:In this clinical trial study, research Society included patients hospitalized with endotracheal tube since the arrival time in intensive care unit. In this study, 30 patients were selected with target-based approach and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The use of a baby toothbrush, which was also used in the present study, has benefits, such as easy and good access to intubated patients' oral cavity, which is almost closed, and also causes less damage and discomfort to be fragile and vulnerable tissues (25). Griffith et al recommended the use of a small soft toothbrush to remove plaque in patients admitted to ICUs because of the possibility of brushing the back of the mouth, as well as cleaning the tongue, gums, and teeth, as quoted by Estaji et al (7).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The use of a baby toothbrush, which was also used in the present study, has benefits, such as easy and good access to intubated patients' oral cavity, which is almost closed, and also causes less damage and discomfort to be fragile and vulnerable tissues (25). Griffith et al recommended the use of a small soft toothbrush to remove plaque in patients admitted to ICUs because of the possibility of brushing the back of the mouth, as well as cleaning the tongue, gums, and teeth, as quoted by Estaji et al (7).…”
Section: Discussionmentioning
confidence: 83%
“…Alone compared to pharmacological methods. For example, Estaji et al (7) showed that using toothbrushes and chlorhexidine was effective in preventing oral lesions. However, they reported that using toothbrushes compared to chlorhexidine led to better improve-ment of the patient's oral health and had a significant effect on reducing oral lesions (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…509 and 2673 further articles were removed based on the screening of titles and abstracts (Figure S1). 14 Fifty‐three full texts were screened, 41 were excluded (Table S3) 15‐55 and 12 studies were included in the final review. Study characteristics are noted in Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…Sejalan dengan penelitian De Lacerda Vidal et al (2017), mengatakan menggunakan toothbrushing dengan 0,12% gel Chlorhexidine gluconate memiliki insiden VAP yang lebih rendah dibanding kelompok control tetapi tidak signifikan. Estaji, et al (2016) mengatakan bahwa toothbrushing menjadi tindakan esensial dalam pelaksanaan oral care pada pasien intubasi. Menyikat gigi dilakukan pada gigi, gusi, palatum, serta lidah.…”
Section: Menjaga Kebersihan Mulut Atau Oral Hygiene Dan Melakukan Gos...unclassified